Seeds of degrowth? The politics of scaling and working in community-supported agriculture co-operatives - Maier, Fabian (2024)
The pursuit of continuous economic growth as necessary, desirable, and limitless informs governments, businesses, and the social relations amongst people. However, in the face of rapidly accelerating ecological breakdown, intensifying social inequalities, and rising geopolitical tensions, the mantra of infinite growth on a finite planet is increasingly put into question by social movements and scholars across academic disciplines. Grounded in longstanding critiques of growth, discourses of degrowth outline counterproposals on how life could be organised towards ecological and human well-being instead of growth. While recent efforts have been made to understand organisational configurations of degrowth, it still remains largely unclear what degrowth means for organisations and forms of organising. In particular, there is a dearth of knowledge about the social processes of alternative organising and the extent to which these are conducive to a degrowth transformation.